Prosocial behaviors of primary education schoolchildren: the influence of cooperative games - Navarro-Patón, R.; Lago-Ballesteros, J.; Basanta-Camiño, S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The aim of this research was to analyze the influence of the application of a didactic unit based on cooperative games on prosocial behaviors of Primary Education students. The participants were 52 schoolchildren (mean age = 10.32 ± .47) from Lugo (Spain). A quasi-experimental pre-postest design was used without a control group. The Appropriate Behaviors in Physical Education and Sports scale has been used as data collection instrument. Results indicated effects of the program on Appropriate skills to lose (p <.001), Appropriate skills to win (p = .045), Appropriate skills during the game (p < .001) and Social skills (p = .002). Data suggest that the application of didactic units or programs based on cooperative games could positively affect students’ prosocial behaviors in physical education lessons.